Identification of patterns in the production of a biologically-active component for food products - Kovaliova, Olena; Tchoursinov, Yuriy; Kalyna, Viktoriia; Koshulko, Vitalii; Kunitsia, E.; Chernukha, Anton; Bezuglov, Oleg; Bogatov, Oleg; Polkovnychenko, Dmytro; Grigorenko, Natalia; Polkovnychenko, Dmytro (PC Тесhnology сеntеr, 2020)
The study reported here has established patterns in the intensive technology for making a biologically active component (the sprouts of legumes) whose germination involved natural fruit acids (citric, malic, grape). The choice of high-quality and safe stimulants is important for the germination of different grain raw materials. Such substances are the fruit acids of natural origin. Their application has made it possible to obtain a high-value component for healthy foods, namely, the sprouts of a variety of legumes. The experimental research has proven the effectiveness of using fruit acids as the effective intensifiers and disinfectants for the process of obtaining the legume sprouts. It has been shown that their use makes it possible not only to intensify the germination of legumes but also contributes to the more active formation of sprouts, and disinfects the seedbed. Thus, the use of aqueous solutions of fruit acids at the concentration of 0.25–1.25 % led to an increase in the following indicators: the germination energy, by 4–7 %; the ability to germinate, by 5–8 %; the length of the sprouts, by 3–11 mm; the weight of the sprouts, from 1 to 12 % depending on the crop. In addition, the composition of the sprouts has been investigated, which confirmed the biological usefulness and rationality of their introduction to the composition of food products as a biologically active component. The reported study has shown that they contain the elevated content of amino acids (by 3–50 % depending on the amino acid), vitamins(В1, В2, В3, В6, В12, РР, Е, С, А), the high content of protein (32 %) and extractive substances (44 %). This testifies to the biological and nutritional value of the sprouts obtained using intensive technology. The investigated technology for making legumes sprouts is innovative. The sprouts obtained can become highly nutritious components for new health food products.
Keywords: biologically active component; fruit acids; citric acid; malic acid; grape acid; legume sprouts